Circulating miR-103a-3p and miR-660-5p are associated with bone parameters in patients with controlled acromegaly. Issue 1 (January 2019) - Valassi, Elena; García-Giralt, Natalia; Malouf, Jorge; Crespo, Iris; Llauger, Jaume; Díez-Pérez, Adolfo; Webb, Susan M
Abstract : Background: Biochemical control of GH/IGF-I excess in acromegaly (ACRO) is associated with persistent impairment of trabecular microstructure leading to increased risk of vertebral fractures. Circulating miRNAs modulate the activity of osteoblasts and osteoclasts, and may be potential biomarkers of osteoporosis. Aims: Identify differentially expressed miRNAs in the serum of patients with controlled ACRO vs controls and correlate miRNA levels with both biochemical and structural bone parameters. Patients and methods: Twenty-seven patients with controlled ACRO (11 males, 16 females; mean age, 48 ± 5 years; BMI, 28 ± 4 kg/m 2 ) and 27 age-, gender- and BMI-matched controls were recruited. Areal BMD at lumbar spine and femur, and trabecular bone score were assessed; volumetric BMD was measured by quantitative computed tomography QCT-Pro (Mindways). Twenty miRNAs, chosen by their putative role in bone, were quantified in serum using real-time qPCR. Results: In ACRO patients, miR-103a-3p and miR-191-5p were found overexpressed, whereas miR-660-5p was underexpressed ( P < 0.001). miR-103a-3p levels were negatively associated with both trabecular vBMD at trochanter and serum osteoprotegerin concentrations ( P < 0.05) and positively with vitamin D concentrations ( P < 0.01) and total cross-sectional area of the femoral neck ( P < 0.05). miR-660-5p levels were correlated with both trabecular vBMD at trochanter and OPG concentrations ( P < 0.05), but were negatively associated with vitamin D levels ( P < 0.05). A negative correlation between miR-103-a-3p and miR-660-5p was found in both groups ( P < 0.001). Conclusions: Circulating miR-103a-3p and miR-660-5p are differentially expressed in controlled ACRO patients and associated with bone structural parameters. miRNAs may be one of the mechanisms involved in the pathogenesis of bone disease and could be used as biomarkers in ACRO patients.